THE EFFECT OF MUSIC INTERVENTION ON PSYCHOLOGICAL DISTRESS OF CARDIOVASCULAR PATIENTS AND CANCER PATIENTS - ROSHAN ANIE ALEX (IMPACT: International Journal of Research in Applied, Natural and Social Sciences (IMPACT: IJRANSS), 2014)
The study was intended to find out the effect of music intervention on the psychological distress of cardiovascular patients and cancer patients. The sample under study for music intervention was 30 female cardiovascular patients and 30 female cancer patients selected from various hospitals in Kerala. The patients were selected based on their willingness to attend the intervention program. The tools used were DASS 21 and music CD recorded with seven songs based on Indian ragas like Hindolam, Abhogi, Hamsadhwani, Sree Ragam, Sreeranjini, Sivaranjani, Revathi, pre-recorded with the help of an expert musician. The results indicated that there were significant differences in their level of depression, anxiety, stress and total psychological distress in both cardiovascular and cancer patients before and after music intervention. Cardiovascular and cancer patients after music intervention had significantly lower level of depression, anxiety, stress and total psychological distress compared to their score on depression, anxiety, stress and psychological distress before music intervention. The results clearly indicated that music have a significant effect on the psychological distress of cardiovascular and cancer patients.